2019
DOI: 10.31028/ji.v14.i1.17-24
|View full text |Cite
|
Sign up to set email alerts
|

Water balance analysis on water management of organic System of Rice Intensification (organic-SRI) in West Java, Indonesia

Abstract: ABSTRAKPenelitian ini dilakukan untuk menganalisa efektifitas irigasi berselang dengan neraca air pada lahan SRI dengan penerapan pupuk organik. Eksperimen dilakukan di Desa Gabus Wetan, Kab. Indramayu, Jawa Barat dari 17 November 2016 sampai 1 Maret 2017. Sensor parameter cuaca dan tanah dipasang di lahan untuk mendapatkan data harian kondisi lapang termasuk pertumbuhan tanaman. Data cuaca seperti hujan, suhu udara, kelembaban udara relatif, dan kecepatan angin dan kedalaman muka air diukur secara otomatis se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…However, reduction in rice yield was also reported by [4,38]. Arif et al [4] summarized 31 published research studies on AWD and concluded that 92% of AWD treatments led to yield decreases compared with continuously flooded treatments. The differences in frequency and threshold of the drying cycles of the AWD, soil types, groundwater table depths, and rice varieties used may contribute to the contrasting results.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…However, reduction in rice yield was also reported by [4,38]. Arif et al [4] summarized 31 published research studies on AWD and concluded that 92% of AWD treatments led to yield decreases compared with continuously flooded treatments. The differences in frequency and threshold of the drying cycles of the AWD, soil types, groundwater table depths, and rice varieties used may contribute to the contrasting results.…”
Section: Introductionmentioning
confidence: 93%
“…Water is essential for growth and development of rice plants. However, continuous flooding irrigation results in a large amount of unproductive water outflows through evaporation, seepage through bunds, runoff, and deep percolation [4][5][6][7]. This causes loss of nutrients from the field and pollution of groundwater supplies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations